2009
DOI: 10.4076/1757-1626-2-7281
|View full text |Cite
|
Sign up to set email alerts
|

Early penile metastasis from primary bladder cancer as the first systemic manifestation: a case report

Abstract: Metastatic involement of penis is an exceptionally rare condition. 77% of the metastases are originated from the pelvic region; prostate and bladder are the most frequent primary locations. Retrograde venous route, retrograde lymphatic route, arterial spread, direct extension, implantation and secondary to instrumentation are the mechanisms of metastasis. Approximately two thirds of all penile metastasis are detected at a mean time of 18 months after the detection of the primary tumor and the remaining one thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Similarly, it has been reported that complete relief pain and priapism can be achieved by locally administering 30Gy in 10 fractions in metastatic bladder urothelial carcinoma [21] and metastatic rectal adenocarcinoma [32] using the 3D conformal technique. On the contrary, priapism symptoms were only partially relieved in earlier case reports [20,28], even with a higher dose (56Gy) [20]. To reconcile the results, it is plausible that the modern conformal radiotherapy technique is better than the field-based technique in terms of ensuring coverage of target and avoiding hotspots or high doses to the organs at risk given the palliative nature of the treatment.…”
Section: Discussionmentioning
confidence: 96%
“…Similarly, it has been reported that complete relief pain and priapism can be achieved by locally administering 30Gy in 10 fractions in metastatic bladder urothelial carcinoma [21] and metastatic rectal adenocarcinoma [32] using the 3D conformal technique. On the contrary, priapism symptoms were only partially relieved in earlier case reports [20,28], even with a higher dose (56Gy) [20]. To reconcile the results, it is plausible that the modern conformal radiotherapy technique is better than the field-based technique in terms of ensuring coverage of target and avoiding hotspots or high doses to the organs at risk given the palliative nature of the treatment.…”
Section: Discussionmentioning
confidence: 96%
“…Primary tumor generally involved the genitourinary tract (69%) followed by gastrointestinal cancer (19%). All described cases were associated with very poor prognosis—variable survival rates from 1 to 24 months—and in all these cases, autopsy has identified multiple coexistent sites of metastasis in the patients [5] , [6] , [7] . Only 2 articles from the recent literature have described a penile metastatic localization from osteosarcoma and cholangiocarcinoma [8] , [9] .…”
Section: Discussionmentioning
confidence: 99%
“…In the present case, the patient had a nonulcerative penile nodule without any overt symptoms. Penile metastases of UC are usually diagnosed by biopsy, and non-invasive methods, such as MRI or color-coded duplex ultrasonography, may be used for disease staging [20]. The optimal treatment for penile metastases requires a multidisciplinary approach that is correlated with the disease extent.…”
Section: Discussionmentioning
confidence: 99%